The Ultimate multimedia handbook. - 4 0 16; 1950- Keyes, Jessica; 5 (New York : McGraw Hill, 1997)
A guide to multimedia tools and techniques, discussing what it is and how it is used, and covering topics such as authoring, animation, video, sound, advanced applications, and the Internet.
Includes bibliographical references and index.
Library Journal
Keywords: 2 -- 0; 6; Multimedia systems.;Multimedia.; 20; 2